Competitors in merger control: Shall they be merely heard or also listened to? - Thomas Giebe; Miyu Lee (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
There are legal grounds to hear competitors in merger control proceedings, and competitor involvement has gained significance. To what extent this is economically sensible is our question. The competition authority applies some welfare standard while the competitor cares about its own profit. In general, but not always, this implies a conflict of interest. We formally model this setting with cheap talk signaling games, where hearing the competitor might convey valuable information to the authority, but also serve the competitor's own interests. We find that the authority will mostly have to ignore the competitor but, depending on the authority's own prior information, strictly following the competitor's selfish recommendation will improve the authority's decision. Complementary to our analysis, we provide empirical data of competitor involvement in EU merger cases and give an overview of the legal discussion in the EU and US.
Keywords: G34; K21; L4; C73; L2; 330; merger control; antitrust; European Commission; signaling; efficiency; competitors; rivals